Effect of Ethanol Leaf Extract of Khat (Catha edulis forsk) on Prefrontal Cortex Oxidative Markers and Hematological Profile of Wistar Rats - Mbina, Solomon Adomi; Mada, Sanusi Bello; Eze, Ejike Daniel; Ajayi, Clement Olusoji; Ifie, Josiah Eseoghene; Usman, Ibe Michael; Terkimbi, Swase Dominic; Pastori, Mujinya; Stellamaris, Kembabazi; Rechael, Mpumbya Jackie; Daniel, Okumu; Odoma, Saidi (Journal of Scientific Research & Reports, 2021)
Aim: This study evaluated the effect of ethanol leaf extract of Catha edulis on the prefrontal cortex oxidative markers and hematological profile of Wistar rats. Study Design: The study design was experimental. Place and Duration of Study: Department of Biochemistry, Kampala International University, Uganda and Faculty of Medicine, Department of Pharmacy, Mbarara University of Science and Technology, Mbarara, Uganda. Between January and May, 2021. Methodology: Fresh C. edulis leaves were collected after on-spot identification, and authenticated before being chopped into small pieces and pulverized mechanically. The powdered material was extracted through cold maceration using 70% ethanol for 72 h. The extract was concentrated in vacuo to dryness at 40oC using rotary evaporator. The lethal dose (LD50) of the crude extract was determined using acute toxicity test. The sub-acute toxicity of the crude extract was evaluated by orally administering daily doses of 250, 500, and 1000 mg/kg to the male Wistar rats for 28 days. The animals were monitored for mortality, behavioral and physiological signs of toxicity. Superoxide dismutase (SOD), Catalase (CAT) activities and Malondialdehyde (MDA) levels were estimated using standard methods. The blood samples were analyzed using the automated hematology analyzer: Mindray BC-6000. Shenzhen, China. Results: The median lethal dose (LD50) of the C. edulis leaf extract was greater than 5000mg/kg b w. The SOD and CAT activities of C. edulis treated groups compared to the control group were significantly (p < 0.05) reduced, the malondialdehyde (MDA) levels were increased in C. edulis treated groups compared to the control group. There was no significant change in the hematological parameters, however, there were slight variations in the WBC and RBC counts in some C. edulis treated groups. Conclusion: Long term chewing of C. edulis could result in oxidative stress. It is therefore important for chronic C. edulis leaf chewers to take caution.
Keywords: Catalase; khat; Lipid peroxidation; Malondialdehyde; Superoxide dismutase